2017
DOI: 10.1007/s13346-017-0448-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-based triggered drug delivery to tumors

Abstract: Over the past few decades, applications of ultrasound (US) in drug delivery have been documented widely for local and site-specific release of bioactives in a controlled manner, after acceptable use in mild physical therapy for tendinitis and bursitis, and for high-energy applications in fibroid ablation, cataract removal, bone fracture healing, etc. US is a non-invasive, efficient, targetable and controllable technique. Drug delivery can be enhanced by applying directed US in terms of targeting and intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 108 publications
0
72
0
1
Order By: Relevance
“…They can be used for Sonopermeation was defined by Snipstad and coworkers as the collective name for pore formation and other additional changes in the BBB permeability due to the microbubbles and ultrasound, such as the opening of tight junctions, stimulated endo-and transcytosis, enhanced perfusion, and stromal alterations [188]. This method has many advantages: 1) It can be focused just on the area of the tumor or diseased parts of the brain; 2) the poration does not require high energy ultrasound, therefore, does not cause damage in intermediery tissues; 3) however, the ultrasound can cause some overheating, just enough to increase blood flow [187,195], vascular permeability [196,197] that also modifies the effectiveness of drug delivery [198][199][200][201] in the target area, and 4) membrane integrity regenerates fast (within hours) after the intervention [202]. However, sonopermeation technique can cause some inflammation in the targeted area [203,204], but does not cause ischemia, neither apoptosis and does not damage neurons [205].…”
Section: Receptor-mediated Openingmentioning
confidence: 99%
“…They can be used for Sonopermeation was defined by Snipstad and coworkers as the collective name for pore formation and other additional changes in the BBB permeability due to the microbubbles and ultrasound, such as the opening of tight junctions, stimulated endo-and transcytosis, enhanced perfusion, and stromal alterations [188]. This method has many advantages: 1) It can be focused just on the area of the tumor or diseased parts of the brain; 2) the poration does not require high energy ultrasound, therefore, does not cause damage in intermediery tissues; 3) however, the ultrasound can cause some overheating, just enough to increase blood flow [187,195], vascular permeability [196,197] that also modifies the effectiveness of drug delivery [198][199][200][201] in the target area, and 4) membrane integrity regenerates fast (within hours) after the intervention [202]. However, sonopermeation technique can cause some inflammation in the targeted area [203,204], but does not cause ischemia, neither apoptosis and does not damage neurons [205].…”
Section: Receptor-mediated Openingmentioning
confidence: 99%
“…However, large diameter bubbles could not pass through the endothelial space of tumor vessels to enter the tumor tissue space, which was not conducive to local drug accumulation. 26 By comparing our experimental results, we found that the TEM group exhibited significantly superior tumor control and apoptosis promotion than the G250-TNBs group, potentially because drugs carried by G250-TNBs were released more slowly within a certain period of time due to the better stability of G250-TNBs. Therefore, the G250-TNBs group had a lower local TEM concentration than the TEM group, and direct use of TEM facilitated the passive diffusion, internalization, penetration, and entry into cells.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally multi-targeted liposomes have been constructed, which can target two of more receptors simultaneously, with the aim to increase their targeting efficiency [49]. Other approaches employ the use of physical methods as stimuli, to further increase the targeting efficiency of ligand-targeted-liposomes, such as magnetic or ultrasound enhanced targeting [50][51][52]. Nevertheless, in addition to other potential problems, the last multifunctional systems may be perhaps too complicated for translation into drug products, a factor that should also be seriously accounted for when searching for solutions in the problem to realize actively targeted liposomes, or any other type of nanoparticles (NPs).…”
Section: Current Bottlenecks In Nanoparticle-assisted Targeted Drug Dmentioning
confidence: 99%